A Janovec‐Kay‐Dunn‐Like Behavior at Thickness Scaling in Ultra‐Thin Antiferroelectric ZrO2 Films (Adv. Electron. Mater. 11/2021). (10th November 2021) - Tasneem, Nujhat; Yousry, Yasmin Mohamed; Tian, Mengkun; Dopita, Milan; Reyes‐Lillo, Sebastian E.; Kacher, Josh; Bassiri‐Gharb, Nazanin; Khan, Asif Islam
Abstract : Ultra‐High Density Memory Antiferroelectric oxides are a promising candidate for next‐generation, ultra‐high density memory technologies. However, operating voltage at size reduction, a major criteria for design of miniaturized devices, has remained unaddressed. In article 2100485, Nazanin Bassiri‐Gharb, Asif Islam Khan, and colleagues show that the critical polar—antipolar transition voltages in prototypical fluorite‐structured antiferroelectric ZrO2 thin films show a –2/3 power law dependence on the average crystallite size, in analogy to the Janovec‐Kay‐Dunn Law for ferroelectrics.